INTERNET DAN SIGNIFIKANSINYA TERHADAP KARYA ILMIAH MAHASISWA - Mutho'in Mutho'in (IAIN Pekalongan, 2014)
This study seeks to uncover the feasibility of internet sites that are used as reference by student and how they cite it in their scientific work. By tracing, analyzing source as a reference, it was found that most of students are still using an unreliable source of internet sites. The most widely used is www.blogspot.com , ww.wordpress.com and wikipedia.org respectively. In terms of how they cite, most students just copy and paste though there are a few spelling corrections on (but not significant), they are still not precisely determine when to use the rules of quoting indirectly or rules of quoting directly.